The impact of insulin resistance, dyslipidemia and high sensitivity C-reactivity protein on carotid intima-media thickness in metabolic syndrome - Gawali, Sangeeta M.; Karandikar, Mahesh S. (International Journal of Research in Medical Sciences, 2021)
Background: Carotid intima-media thickness (CIMT) is a strong predictor of cardiovascular events and associated with metabolic syndrome (MetS). The CIMT has been widely used as one of the parameters of atherosclerosis. The aim of the study was to evaluate the impact of insulin resistance, dyslipidemia and high sensitivity C-reactive protein on carotid intima-media thickness in metabolic syndrome patients of Western Maharashtra as very sparse data is available. Methods: It was a cross-sectional study of 400 adults (200 cases and 200 control), 18-50 years of age, both the sexes randomly selected from diabetes and obesity OPD at tertiary care hospital. Diagnosis of metabolic syndrome was done according to modified NCEP adult treatment panel III criteria. CIMT was measured by B mode ultrasound (Philips HT-11, Color Doppler), hs-CRP by ELISA method (Cal biotech). Insulin resistance by HOMA-IR (Homeostatic model assessment of insulin resistance). The predictors of CIMT with various variables were studied by multiple linear regression analysis. Results: We found significant increase in CIMT (0.7895±0.110, p<0.001) in MetS and a positive correlation of CIMT with age, waist to hip ratio, triglyceride levels and systolic blood pressure (p<0.001). Conclusions: Increased carotid intima-media thickness in metabolic syndrome may increase the risk of having a stroke and cardiovascular mortality. It was considered an early deterioration in the arterial intima and is a preclinical stage of atherosclerosis. Early diagnosis and prevention may help to reduce the risk of stroke and cardiovascular mortality.